Comparative evaluation of three different materials: mineral trioxide aggregate, triple antibiotic paste, and abscess remedy on apical development of vital young permanent teeth - Hanmanth Reddy Eppa; Ravindar Puppala; Balaji Kethineni; Sunitha Banavath; Pratej Kiran Kanumuri; Gangamolu Venkateshwara Sai Kishore (Wolters Kluwer Medknow Publications, 2018)
Aims: The aim of the study is to compare the success rate of mineral trioxide aggregate (MTA), Triple antibiotic paste, and Abscess remedy in apical development of vital young permanent teeth. Subjects and Methods: A total of 60 children aged 6-14 years were selected and were randomly divided into three groups, each comprising of 20 children. Group I, Group II, and Group III in which MTA (Pro root), triple antibiotic paste (3Mix MP), and Abscess remedy (Product Dentaire, Switzerland) was used pulpotomy medicament. The children were recalled 1, 6, 9, 12, 18, and 24 months for clinical and radiographic evaluation and were designed as single-blinded randomized clinical trial. Statistical Analysis Used: Chi-square test. Results: The follow-up evaluations revealed that 56 teeth appeared to be clinically and radiographically successful at 24 months' postoperative evaluation. Four teeth treated with Abscess remedy reported pain and periapical lesion. Conclusions: Overall success rate for all the material was 93%, MTA and Triple antibiotic paste have shown 100% success rate, and Abscess remedy has shown 80% success rate.